Strategi dan Analisa Dampak Positif Program Pembinaan Kesadaran Bela Negara di Indonesia - Ananto, Dwi; Rofii, Muhammad Syaroni, Mr. (UI Scholars Hub, 2021)
Nowadays, it is easy for cultures and ideologies from other countries to come to take advantage of technological developments. The purpose of this research is to find variables that significantly affectthe implementation of the State Defense Awareness Development Program, namely the number of internet users, the Human Development Index and the Cultural Community. Another objective is tofind out strategies that can be taken to improve the implementation of the State Defense Awareness Development Program and to analyze the positive impact of the implementation of the State Defense Awareness Development Program. The research design was carried out using mixed methods with sequential explanatory methods. The research findings indicate that the internet is the most signifi-cant variable that can influence the success of the State Defense Awareness Development Program,and by using a SWOT analysis, it is found that what must be done so that implementation is carriedout well is to carry out a strategy to increase activities from what has been done previously. Analysisofthe positive impacts ofthe implementation oftheState Defense Awareness Development Programthat based on the survey carried out the most possible approach in counteracting the negative impacts of globalization is an approach to increasing the love for the homeland towards citizens, namely theState Defense Awareness Development program. Keywords: Defending the Country, Nationalism, Globalization